Peptide precursors that acquire denatured collagen-hybridizing ability by O-to-N acyl migration at physiological pH. Issue 15 (25th March 2020) - Kanai, Sayaka; Machida, Koshi; Masuda, Ryo; Koide, Takaki
Abstract : Collagen-like peptides containing Gly-Ser O -acyl isopeptide units without self-assembling propensity serve as precursors for collagen-detecting agents. Abstract : Here, we report peptide probes with either single or cyclic double stranded collagen-like sequences that spontaneously acquire collagen-hybridizing ability at physiological pH. These peptides have ester bonds derived from O -acyl isopeptide units that are converted to amide bonds via intramolecular O -to- N acyl migration by a pH shift. The peptides that do not require pre-treatment for disassembly will be useful as prodrugs in theranostic treatments targeting unfolded collagen.